Is the rapid initial performance loss of Fe/N/C non precious metal catalysts due to micropore flooding?. Issue 1 (15th December 2016) - Choi, Ja-Yeon; Yang, Lijun; Kishimoto, Takeaki; Fu, Xiaogang; Ye, Siyu; Chen, Zhongwei; Banham, Dustin
Abstract : The instability of Fe/N/C non-precious metal catalysts is still not fully understood, and must be overcome before these catalysts can be commercialized. Abstract : The activity of non-precious metal catalysts (NPMCs) has now reached a stage at which they can be considered as possible alternatives to Pt for some proton exchange membrane fuel cell (PEMFC) applications. However, challenges still remain in achieving acceptable stability (performance during potentiostatic or galvanostatic experiments). The most widely reported hypotheses for the instability of NPMCs include de-metalation, protonation/anion binding, and generation of H2 O2 . Recently, it has been proposed that the largest contribution to the instability of NPMCs is from flooding of micropores within the catalyst particles leading to significant mass transport limitations. While indirect evidence has been obtained that appears to support this hypothesis, no study has yet been performed to directly target micropore flooding. In this work, a systematic study is performed to investigate micropore flooding in situ before and after stability testing. The results do not support micropore flooding as being a large contributor to instability, at least for the family of NPMCs evaluated in this work. The protocol outlined here can be used by other researchers in the NPMC community to diagnose micropore flooding in their own respective catalysts.